High frequency, high power conversion through PWM switching using the third generation IGBTS - Ali Iftekhar Maswood (2008)
Insulated gate bipolar transistor (IGBT) continues to find wide use in inverter applications due to the combined benefits of both bipolar junction transistor and metal-oxide-semiconductor field-effect transistor. This device is now playing an important role whether in machinery or factory automation, dominating power electronic system using motor drives in the medium voltage and medium power range. Essentially, IGBT has low turn-on and turn-off energy loss, low on-state loss and is easy to drive. Present methods of computing the IGBT switching loss can be classified as measurement based technique or using mathematical model to represent it, which results in over simplified expressions. In order to model the power loss of a threephase IGBT inverter accurately, we proposed to calculate the IGBT device switching loss based on instantaneous voltage and current values. The proposed methods of calculation were then found to be in good agreement with simulation, data sheet and experimental values. To date, IGBT device can handle high current rating, medium voltage and frequency. However, as the switching frequency increases, switching power losses increase too and will become the dominant factor in the total power loss calculation. This greatly restricts the possibility of switching at high frequency and high power using conventional sinusoidal pulse width modulation (SPWM) technique. This limitation restricts the use of IGBT in either power rating over 50kVA at low frequency around 2kHz applications or low power rating under 20kVA at high frequency over 5kHz in the SPWM hard switching operation. In order to apply PWM switching in relatively high power high frequency application, this research work also discusses on the novel employment of PWM switching through a technique known as PWM-specific harmonic elimination (PWM-SHE) method. A three-phase line-to-neutral PWM-SHE switching function consisting of two-level switching is utilized in the circuit. Essentially, to eliminate the same number of low order harmonics, PWM-SHE requires the use of 50% less switching pulse over the conventional carrier modulated SPWM method. This automatically implies less stress on the switching device and hence less switching loss.